PENERAPAN MODEL PEMBELAJARAN TGT (TEAMS GAMES TOURNAMENT) BERBANTUAN MEDIA MATH CHESS UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA FASE B - Indah Sekar Wangi; Abdul Mujib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is based on low student learning outcomes, a lack of interest in learning, and the continued use of conventional methods in mathematics instruction. This study aims to determine the effectiveness of implementing the Teams Games Tournament (TGT) learning model assisted by Math Chess media in improving mathematics learning outcomes for Phase B students at Taman siswa Galang Private Elementary School. The research method used is Classroom Action Research (CAR), which was conducted in two cycles, with each cycle consisting of planning, action implementation, observation, and reflection stages. Data collection instruments included observation, learning outcome tests, and documentation. The research results show an improvement in student learning outcomes from cycle I to cycle II. The implementation of the TGT model combined with Math Chess media has proven capable of creating a fun, interactive, and competitive learning environment, making students more active, enthusiastic, and able to easily understand multiplication concepts. In conclusion, the TGT learning model assisted by Mathchess media is effective in improving students' mathematics learning outcomes on multiplication material in class III at the Private Elementary School Taman siswa Galang.